Food insecurity and its determinants in a vulnerable area of Santiago, Chile - Pinheiro, Anna Christina [UNESP]; Quintiliano-Scarpelli, Daiana; Araneda-Flores, Jacqueline; Oliveira, Rogerio Antonio de [UNESP]; Pizarro, Tito; Suarez-Reyes, Mónica; Marques de Oliveira, Maria Rita [UNESP] (Frontiers, 2022)
This study aims to identify the determinants associated to food insecurity in a group of households composed of schoolchildren and their mothers/caregivers, who lived in a low-to-medium community development index area of the city of Santiago, Chile with a high presence of migrant population. The non-probabilistic and convenience sample was made up of 646 people, who answered a series of surveys with the aim of characterizing this group in sociodemographic terms (sex, age, number of inhabitants in the household, place of food purchase, conditional or non-conditional state transfer program beneficiary status, persons in charge of purchasing food for the household, mothers/caregivers education level and basic knowledge of food and nutrition). To assess moderate-to-severe food insecurity and severe food insecurity, the Food Insecurity Experience Scale-FIES was applied between September and October 2021. Logistic regression analysis were used to carry out multivariate analyses, with the use of stepwise back-and-forward strategies for the selected variables and defining p < 0.05. These models were adjusted per number of inhabitants in the household. The results indicate that 25.4% of households presented moderate-to-severe food insecurity, and 6.4% severe food insecurity experience. The variables that presented significant odds of risk to food insecurity were being a migrant, low maternal education level, low performance on basic knowledge in nutrition and when the father was responsible for food purchases. Several public policies have been implemented in Chile during the most recent decades aimed at increasing access to healthier foods and the implementation of healthier food environments. Despite this, there are still social and economic health determinants that contribute to the risk of odds insecurity for the most vulnerable groups in the country, thus putting at risk the fulfillment of the human right to adequate food at risk.
Keywords: Chile; food and nutrition; food insecurity; Food Insecurity Experience Scale; maternal education; migrant; public policies